An Analysis of Students’ Difficulties in Speakings Skill at Tenth Grade of SMAN 8 Jambi City - Dinata, Diva; Fitri, Nurul; Dinata, Ridho Praja (Universitas Batanghari Jambi, 2025)
Students’ difficulties in speaking skill at tenth grades of SMA N 8 Jambi City that the main problems they face in learning speaking skills are a lack of vocabulary, the need for articulation, the need to speak without hesitation, and anxiety of making mistakes when speaking. This research is on students' difficulties in speaking English at the tenth grade of SMA N 8 Jambi City. The aim of this study is to describe the contributing factors of students' difficulties in speaking English at the tenth grade of SMA N 8 Jambi City. In this study, the researcher used the descriptive qualitative method. The researcher collected the data by questionnaire and interview. The data was analyzed by reducing the data, displaying the data, and drawing or verifying conclusions. The result of this study is that students' difficulties in speaking English are influenced by two factors, namely linguistic factors and psychological factors. Linguistic factors consist of a lack of vocabulary, a lack of pronunciation, and a lack of grammar, while psychological factors are a lack of confidence, shyness, and fear of making mistakes.